2019
DOI: 10.1126/science.aaw7765
|View full text |Cite
|
Sign up to set email alerts
|

Blocking α 4 β 7 integrin binding to SIV does not improve virologic control

Abstract: A study in nonhuman primates reported that infusions of an antibody against α4β7 integrin, in combination with antiretroviral therapy, showed consistent, durable control of simian immunodeficiency virus (SIV) in rhesus macaques. The antibody used has pleiotropic effects, so we set out to gain insight into the underlying mechanism by comparing this treatment to treatment with non-neutralizing monoclonal antibodies against the SIV envelope glycoprotein that only block α4β7 binding to SIV Env but have no other ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
5
28
2
Order By: Relevance
“…the likelihood of α 4 β 7 integrin binding motif-directed V2-specific antibody binding. In nonhuman primates targeting α 4 β 7 integrin with a primatized mAb protected animals from repeated low-dose intravaginal SIV challenge (36)(37)(38), but a follow-up SIV infection study found that the same antibody had no effect on virological control (39). Blocking Env-α 4 β 7 integrin in vitro did not inhibit CD4 + T cell infection (40).…”
Section: Discussionmentioning
confidence: 99%
“…the likelihood of α 4 β 7 integrin binding motif-directed V2-specific antibody binding. In nonhuman primates targeting α 4 β 7 integrin with a primatized mAb protected animals from repeated low-dose intravaginal SIV challenge (36)(37)(38), but a follow-up SIV infection study found that the same antibody had no effect on virological control (39). Blocking Env-α 4 β 7 integrin in vitro did not inhibit CD4 + T cell infection (40).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of anti-α4β7 mAb administered in SIVinfected RMs during ART continues to be a highly debatable issue. While an earlier study showed that this treatment can limit viral rebound after ART interruption (21), more recent pre-clinical (23)(24)(25) and clinical (41) studies did not show any significant benefit from anti-α4β7 mAb treatment in ARTsuppressed, HIV-infected individuals or SIV-infected RMs in inducing viral remission in the absence of ART (42). Recently, using samples obtained from various gastrointestinal sites from IBD/CD patients, it was found that anti-α4β7 therapy led to a significant reduction of lymphoid aggregates, mostly in the terminal ileum (43).…”
Section: Discussionmentioning
confidence: 99%
“…IL-21 and anti-α4β7 mAbs have been previously administered as single interventions in naive or SIV-infected RMs with an acceptable safety profile (10,18,(21)(22)(23)(24)(25). However, combined administration of the two reagents has not yet been tested.…”
Section: The Combined Administration Of Il-21 and Anti-α4β7 Mab Is Samentioning
confidence: 99%
“…Blocking of α4β7 in monkey models showed promise for prevention of SIV infection and for viral control in SIV-infected monkeys [39,40]. However, the latter results were not substantiated in recent studies of nonhuman primates [41][42][43] or HIV-infected patients [44].…”
Section: Expression Of Lfa-1 Integrin On Cd4+ T Cells Promotes Hiv Enmentioning
confidence: 97%